2016
DOI: 10.1186/s12863-016-0338-9
|View full text |Cite
|
Sign up to set email alerts
|

Focal exposure of limited lung volumes to high-dose irradiation down-regulated organ development-related functions and up-regulated the immune response in mouse pulmonary tissues

Abstract: BackgroundDespite the emergence of stereotactic body radiotherapy (SBRT) for treatment of medically inoperable early-stage non-small-cell lung cancer patients, the molecular effects of focal exposure of limited lung volumes to high-dose radiation have not been fully characterized. This study was designed to identify molecular changes induced by focal high-dose irradiation using a mouse model of SBRT.ResultsCentral areas of the mouse left lung were focally-irradiated (3 mm in diameter) with a single high-dose o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…To mimic the effects of clinical radiotherapy in an animal model of IR-induced lung damage, we had previously exposed mice lungs to high-dose radiation using a small-animal micro-irradiator (X-RAD320) equipped with a collimator system (to produce focal radiation beams) 7,8,28 . These studies showed that radiation pneumonitis occurs in mice within 2 weeks of exposure to 60-100 Gy of IR 8,15,28 .…”
Section: Lxa 4 Inhibits Radiation-induced Lung Inflammatory Responsesmentioning
confidence: 99%
See 2 more Smart Citations
“…To mimic the effects of clinical radiotherapy in an animal model of IR-induced lung damage, we had previously exposed mice lungs to high-dose radiation using a small-animal micro-irradiator (X-RAD320) equipped with a collimator system (to produce focal radiation beams) 7,8,28 . These studies showed that radiation pneumonitis occurs in mice within 2 weeks of exposure to 60-100 Gy of IR 8,15,28 .…”
Section: Lxa 4 Inhibits Radiation-induced Lung Inflammatory Responsesmentioning
confidence: 99%
“…Modern clinical radiotherapy techniques, including stereotactic radiotherapy (SBRT)-which delivers small fractions of ablative radiation doses-are more accurate and precise than conventional radiotherapy techniques. Previously, we had developed a mouse model that simulates SBRT; we used an image-guided smallanimal IR system to deliver a single high dose of radiation to the lung and verified the induction of pulmonary fibrosis in response to IR [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assuming close to zero mortality and very limited morbidity of the surgical procedure, as typified by the study mentioned above, it does not seem realistic to think that the radiation technique can outperform surgery. The only way this seems possible is if the radiation somehow induces the patient's own immune system to help with cancer surveillance and treatment which has been suggested by some preclinical studies (3). Nonetheless this is quite a stretch and the reason most of the data coming out now that compares stereotactic radiation for small lung cancers with surgical resection favors surgical resection particularly when propensity-matching is done to balance the comparison populations.…”
mentioning
confidence: 99%